EFFORTS TO INCREASING THE MANAGEMENT OF "FOUR BROTHERS" TEMPE INDUSTRY PRODUCTION IN VILLAGE OF TEMPE, TENGGILIS KAUMAN - juliani pudjowati (XXXXX, 2022)
Tempe is a folk food, more and more people like tempeh for side dishes or snacks so that the demand for tempe increases. The demand for tempeh is not only among households but also hotels and restaurants. The development process of the Tempe industry in Tenggilis Kauman Surabaya, especially the Tempe "Four Brothers" basically has the aim of improving the quality and production of tempeh, but in fact it has some obstacles. For example, less skilled and poorly trained workers ,lack of capital, weak access to the broader market, weak mastery of technology, poor organizational management systems and lack of cooperation with other entrepreneurs against large companies are also significant obstacles. The feasibility of a business by looking at the potential profit generated. Therefore, business management systems, production processes, production facilities, marketing and target markets are needed to be calculated and carried out in a planned and measurable manner in an effort to get the expected results